Potential of Oncostatin M to accelerate diabetic wound healing. Issue 4 (1st November 2012) - Shin, Soo Hye; Han, Seung‐Kyu; Jeong, Seong‐Ho; Kim, Woo‐Kyung
<x xml:space="preserve">Abstract</x> Oncostatin M (OSM) is a multifunctional cytokine found in a variety of pathologic conditions, which leads to excessive collagen deposition. Current studies demonstrate that OSM is also a mitogen for fibroblasts and has an anti‐inflammatory action. It was therefore hypothesised that OSM may play an important role in healing of chronic wounds that usually involve decreased fibroblast function and persist in the inflammatory stage for a long time. In a previous in vitro study, the authors showed that OSM increased wound healing activities of diabetic dermal fibroblasts. However, wound healing in vivo is a complex process involving multiple factors. Thus, the purpose of this study was to evaluate the effect of OSM on diabetic wound healing in vivo. Five diabetic mice were used in this study. Four full‐thickness round wounds were created on the back of each mouse (total 20 wounds). OSM was applied on the two left‐side wounds (n = 10) and phosphate‐buffered saline was applied on the two right‐side wounds (n = 10). After 10 days, unhealed wound areas of the OSM and control groups were compared using the stereoimage optical topometer system. Also, epithelialisation, wound contraction and reduction in wound volume in each group were compared. The OSM‐treated group showed superior results in all of the tested parameters. In particular, the unhealed wound area and the reduction in wound volume demonstrated statistically significant differences (P < 0·05). The results of this study indicate that topical application of OSM may have the potential to accelerate healing of diabetic wounds.